Diseño del sistema HACCP para el proceso de producción de carne bovina para consumo (2003)
ABSTRACT: The objective of this work was to design the Hazard Analysis Critical Control Points - HACCP system for the meat production process in two sections, preharvest section and harvest section. Preharvest section was constituted for two beef cattle farms located in the municipality of Caucasia (breeding component) and in the municipality of Jericó (growing - fattening component), in year 2001. Harvest section was constituted for the slaughterhouse of the Central Ganadera S. A. in the municipality of Medellín, in year 2001. A descriptive study of a typical case of the meat production process was conducted. Each section step was studied and the seven principles of the HACCP system were applied. Information was obtained through primary sources (interviews to administrative and operative personnel, observation of routine processes) and secondary sources (documentedinformation). As main results one critical control point (CCP) type 2 was determined for preharvest section and ten CCP type 2 and one CCP type 1 were determined for harvest section. Critical limits for CCP, corrective measures for CCP and a CCP monitoring system were established. The most important conclusions shows that HACCP system design represents an important component of the meat safety assurance program and consequently will contribute to consumers health protection. To achieve HACCP system implementation it is necessary to have prerequisites like Standard Operating Procedures, Good Farming Practices (including appropriate use of plague killers and veterinary drugs), and Good Manufacturing Practices (including cleaning/disinfecting program and arthropods and rodents control program). The quarantine step is the only CPP (CPP type 2) along preharvest section, due to its importance to prevent entrance of animals to next steps carrying diseases acquired in previously. Antemortem inspection step and postmortem inspection step, CPP 2 and CCP 1, respectively, are the fundamental base used for recognition, minimization and elimination of microbiological, chemical and physical hazards form final product. The pre-shipping room lacking of regulated temperature estimulates bacterial growth due to high temperatures that can affect the product safety. Shipping step represents, in some cases, one of most important CCP within HACCP system design due to unsafe shipping and transport procedures, which represents potential contamination and an effort waste looking for food safety assurance on previous steps.